The sovereignty cartel / J. Samuel Barkin, University of Massachusetts Boston. - Barkin, Samuel, 1965- (Cambridge University Press, 2021)
"Sovereignty is often talked about as central to, even definitional of, contemporary international relations. We assume it as the source of state authority or use it to describe state capabilities. We talk about whether it is getting weaker, and occasionally about whether it is changing in some fundamental way. But rarely do we get into details about what it is, how it works, how it maintains itself, and what the effects are of sovereignty specifically, as opposed to some other organizing principle, on contemporary international relations. In this context, some of the patterns of state behavior that are easy to take for granted as part of the sovereign states system are in fact striking. States do not just compete with each other to maximize the national interest or cooperate with each other to provide global public goods. They also collude with each other to reinforce the centrality of the sovereign state as a category of actor in international relations. This pattern of collusion is what I call the sovereignty cartel"-- Provided by publisher.
Keywords: Sovereignty.; International relations.